Horyzons USA: A moderated online social intervention for first episode psychosis. Issue 2 (17th February 2020) - Ludwig, Kelsey A.; Browne, Julia W.; Nagendra, Arun; Gleeson, John F.; D'Alfonso, Simon; Penn, David L.; Alvarez‐Jimenez, Mario
Abstract: Aim: We evaluated the feasibility and acceptability of Horyzons, an online social media platform designed to facilitate relationship development among, and introduce therapeutic content to, first‐episode psychosis (FEP) clients. We also evaluated whether participation in the platform was related to reduced loneliness, improved social integration and increased psychological well‐being. Methods: Twenty‐six participants diagnosed with a schizophrenia spectrum disorder were provided access to the moderated Horyzons platform for 12 weeks. During the intervention period, participants were encouraged to access therapeutic content and social components embedded within the site. Participants were recruited from three first‐episode coordinated specialty care clinics in North Carolina and assessed at four time points: baseline, mid‐treatment, post‐treatment and 1‐month follow‐up. Results: Findings indicated that Horyzons was both feasible and very well tolerated, with a 92.3% retention rate and 79.2% of participants actively engaged in the platform. The most commonly identified personal strengths selected by Horyzons users were creativity (61.5%), curiosity (42.3%) and courage (38.5%). Feedback from participants indicated Horyzons could be improved by the development of a smartphone application, expanding the size of the Horyzons community and facilitating private messages between users. Preliminary results with engaged participants showed the greatest improvements in psychosis‐related symptoms, followed by self‐reported experience of negative emotions, depressive symptoms and loneliness. Conclusions: This open trial found that Horyzons is both feasible and acceptable to FEP persons early in the course of illness living in the United States.